Post-weaning development of beef bulls: impacts of omega-3 supplementation and accuracy of nutrient requirement-based predictions - Fraser, Brandon Joseph (My University, 2025)
Two studies were conducted to evaluate (1) the effects of omega-3 fatty acid supplementation on post-weaning development of beef bulls and (2) the accuracy of nutrient requirement model predictions for feed intake and growth in developing bulls. In the first study, spring-born Angus, Hereford, and Simmental bulls were weaned each September and developed at the Kansas State University Precision Feed Intake Facility using Insentec® bunks for individual DMI collection. The effects of supplementing an omega-3 fatty acid-based product on growth performance and reproductive development of post-weaning beef bulls were evaluated in two experiments. In Experiment 1, bulls (n = 42; 352 ±19 kg; 292 ± 6.3 d of age) were stratified by BW and age and randomly assigned to one of three omega-3 supplement levels added to a common corn silage and wet corn gluten feed-based growing diet: 0.0 (CON), 0.22 (MOD), or 0.43 (HI) kghd/d (DM basis). Treatments were applied for about 60 d. Dry matter intake did not differ among treatments (P = 0.64). Bulls receiving the HI treatment had greater ADG (P ≤ 0.05) compared with CON and MOD, although final BW and gain to feed ratio were similar (P ≥ 0.52). Scrotal circumference and serum fatty acids were unaffected (P ≥ 0.67). Supplementation increased IMF% (P = 0.03) in MOD and HI and tended to increase LMA in MOD (P = 0.06). Rib fat did not differ (P = 0.50). In Experiment 2, bulls (n = 39; 332 ±14 kg; 291 ± 6.3 d of age) received identical supplementation treatments for 80 d using an isonitrogenous formulated corn silage and dried distillers grains-based diet with corn germ meal as an added protein source. Final BW (P = 0.86), ADG (P = 0.49), and DMI (P = 0.39) did not differ. Gain to feed tended to differ (P = 0.08), but SC, IMF%, LMA, and rib fat were not affected (P ≥ 0.61). Initial serum fatty acids were similar among treatments, but by d 80 supplemented bulls had greater omega-3 concentrations and a lower omega-6:omega-3 ratio (P < 0.01); MOD also had greater total FA and SFA than CON (P = 0.03), with HI intermediate. Omega-3 supplementation at 0.22 and 0.43 kg per hd per day improved growth performance in Experiment 1, but no performance differences occurred in Experiment 2 when diets were formulated to be isonitrogenous, indicating that responses were likely driven by dietary protein rather than omega-3 inclusion. For the second study, a four-year retrospective analysis of purebred bull performance (2021 to 2024; n = 154) compared observed performance with predictions from the BRaNDS Growing Bull module. Actual DMI averaged 1.69 to 9.29 kg/hd per d while predicted DMI averaged 9.10 kg/d (bias = -0.20 kg/d). Correlations between observed and predicted DMI were moderate across years (r = 0.55 to 0.56; P < 0.01) and stronger within individual years (r = 0.71 to 0.84). Actual ADG averaged 0.34 to 1.61 kg/d, whereas the BRaNDS model predicted 1.04 to 1.21 kg/d, generating underprediction biases of -0.50 to -0.57 kg/d. Year-specific ADG biases were -0.76, -0.51, -0.84, and +0.07 kg/d for years 1 through 4, respectively, and corresponding DMI biases were +1.23, +0.42, -1.15, and -1.18 kg/d. Adjusting BRaNDS inputs for temperature, mud, body condition score, or mature BW did not meaningfully improve accuracy. These results show that BRaNDS equations moderately predict DMI but consistently underestimate ADG of growing beef bulls under the constraints utilized in this retrospective analysis. Refinement of metabolizable energy and protein equations, as well as additional use of individual animal intake and performance data collected under various model input constraints are needed to improve accuracy of prediction models.
Keywords: Bulls; Omega-3 fatty acids; Dry matter intake; Average daily gain; Nutrient requirement models